Optimal plateau pressure for patients with acute respiratory distress syndrome: a protocol for a systematic review and meta-analysis with meta-regression. Issue 5 (29th May 2017) - Yasuda, Hideto; Nishimura, Tetsuro; Kamo, Tetsuro; Sanui, Masamitsu; Nango, Eishu; Abe, Takayuki; Takebayashi, Toru; Lefor, Alan Kawarai; Hashimoto, Satoru
Abstract : Introduction: Lower tidal volume ventilation in patients with acute respiratory distress syndrome (ARDS) is a strategy to reduce the plateau pressure and driving pressure to limit ventilator-induced lung injury (VILI). Several randomised controlled trials (RCTs) and meta-analyses showed that limiting both the plateau pressure and the tidal volume decreased mortality, but the optimal plateau pressure to demonstrate a benefit is uncertain. The aim of this systematic review is to investigate the optimal upper limit of plateau pressure in patients with ARDS to prevent VILI and improve clinical outcomes using meta-analysis with and without meta-regression. Methods and analysis: RCTs comparing two mechanical ventilation strategies will be included, with lower plateau pressure and with higher plateau pressure, among patients with ARDS and acute lung injury. Data sources include MEDLINE via the NCBI Entrez system, Cochrane Central Register of Controlled Trials (CENTRAL), EMBASE and Ichushi, a database of papers in Japanese. Two of three physicians will independently screen trials obtained by search for eligibility, and extract data from included studies onto standardised data recording forms. For each included trial, the risk of bias and the quality of evidence will be evaluated using the Grading of Recommendation Assessment Development and Evaluation system. Ethics and dissemination: This study does not require ethical approval. The results of this systematic review and meta-analysis with and without meta-regression will be disseminated through conference presentation and publication in a peer-reviewed journal. Trial registration number: CRD42016041924